Tττ-framework for the evaluation and improvement of phase behaviour description with the NRTL activity coefficient model - Lamprecht, Danielle Lee (Stellenbosch : Stellenbosch University, 2025)
Lamprecht, D. L. 2025. Tττ-Framework for the Evaluation and Improvement of Phase Behaviour Description with the NRTL Activity Coefficient Model. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/7b47d63c-94b3-450c-846b-9e9baaad1e00